Education in traditional society: parents, children and teachers in El Secretario - Díaz Balado, Alicia (Historia y Memoria de la Educación, 2019)
Letter collections served as correspondence manuals for transmitting norms of epistolary writing in the 19th century.. This article begins with a short presentation of the epistolar book El Secretario and its use in the realm of education. We analyze its content in the light of the teacher-student relationship, the professionalization of teaching and pedagogical renovation. The selected letters of El Secretario, A un estudiantillo and Contestación del estudiantillo show parent-child relationship, in the context of the epistolary narrative, while also allowing for a fundamental pedagogical analysis. This analysis offers insights into the significance of the master-disciple relationship, the influence of reform pedagogy and the role played by letter-writing, both for children’s self-expression and as a means of paternal control from a distance